PENGARUH SEKTOR RIIL DAN KEUANGAN SYARIAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA TAHUN 2007-2014 - Cahyaningrum, Ina Sholati (An-Nisbah: Jurnal Ekonomi Syariah, 2017)
Abstract: The research objectives of this research are to examine signifcantÂ infuence of real sector of manufacture industry, real sector of trade, hotel, andÂ restaurant, syariah fnance of syariah bank and syariah fnance of paymentÂ bank of syariah community to the growth of economy in Indonesia whetherÂ partial or simultan. The rsearch was used quantitative approach which usedÂ associative research. The taking of sample used nonprobability samplingÂ technique and purposive sampling tehnique. The data used are secunder dataÂ which are gotten by triwulan data of gross domestic bruto based on constantÂ price and from statistic report of syariah bank in year 2007-2014. The dataÂ accumulation are documentation and document study. The research was usedÂ method of clasic assumptsion experiment analysis, the experiment of doubledÂ linier regression, hypotheses experiment, and the experiment of determinationÂ coefsien. The result of the reaserch showed that partially (individually), theÂ syariah fnance of syariah bank infuenced positively and signifcantly toÂ the growth of economy in Indonesia and syariah fnance of syariah bankÂ and syariah fnance of payment bank of syariah community infuencedÂ positively and signifcantly to the growth of economy in Indonesia. Meanwhile,Â simultaneously (collective) between the fnancial of syariah bank and syariahÂ fnance of payment bank of syariah community infuenced signifcantly to theÂ growth of economy in Indonesia. For variable of real sector in manufactureÂ industry and real sector of trade, hotel and restaurant statistically couldnâtÂ be continue, because in data excemination showed that there was problem ofÂ Multikolinieritas. So, the researcher took an action to delete variable whichÂ by Multikolinieritas by the reason if that problem was solred by using PCAÂ prosedure. There is only one factor which represented all of free independentÂ variable, so when picturing the similarity of factor regretion could be representedÂ of each free variable to dependent variable, because it could not be seen whichÂ variable having the positive connection and which variable having negativeÂ connection to dependent variable.Keywords: Real Sector, Syariah Finance, and Economy Growth